2013
DOI: 10.1007/s00280-013-2368-6
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled study of gemcitabine plus S-1 combination chemotherapy versus gemcitabine for unresectable pancreatic cancer

Abstract: GS therapy improved PFS and ORR with acceptable toxicity profile in patients with unresectable pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 23 publications
3
34
1
1
Order By: Relevance
“…There were no publication biasesdetected by Egger test for the studies in all of our analysis, in the primary endpoint of OS (t=0.74, p=0.474) and PFS (t=0.35, p=0.738) (Higgins et al, 2002;Higgins et al, 2003;Huai et al, 2013). Each article included in the composition of the funnel plot did not find significant bias (Berlin et al, 2002;Scheithauer et al, 2003;Ohkawa et al, 2004;Di Costanzo et al, 2005;Riess et al, 2005;Herrmann et al, 2007;Bernhard et al, 2008;Cunningham et al, 2009;Nakai et al, 2012;Ozaka et al, 2012;Ueno et al, 2013;Sudo et al, 2014).…”
Section: Influent Analysis and Publication Bias Evaluationmentioning
confidence: 62%
See 1 more Smart Citation
“…There were no publication biasesdetected by Egger test for the studies in all of our analysis, in the primary endpoint of OS (t=0.74, p=0.474) and PFS (t=0.35, p=0.738) (Higgins et al, 2002;Higgins et al, 2003;Huai et al, 2013). Each article included in the composition of the funnel plot did not find significant bias (Berlin et al, 2002;Scheithauer et al, 2003;Ohkawa et al, 2004;Di Costanzo et al, 2005;Riess et al, 2005;Herrmann et al, 2007;Bernhard et al, 2008;Cunningham et al, 2009;Nakai et al, 2012;Ozaka et al, 2012;Ueno et al, 2013;Sudo et al, 2014).…”
Section: Influent Analysis and Publication Bias Evaluationmentioning
confidence: 62%
“…Ueno et al presented that the median OS for GEM combined with S-1 was 10.1 months and 8.8 months for GEMalone. Sudo et al (2014) showed that the median OS for GEM combined with S-1 was 8.6 months and 8.6 months for GEMalone. And in our conclusion, we found that there was significantly better :http://dx.doi.org/10.7314/APJCP.2015.16.14.5681 Gemcitabine+Fluoropyrimidine Combinations for Advanced Pancreatic Cancer -an Updated Meta-Analysis outcome in Group Gem + S-1 vs. Gem (HR,0.83;95% CI,p=0.011;).…”
Section: Discussionmentioning
confidence: 99%
“…Four eligible trials were identified (23)(24)(25)(26). Characteristics of these trials, including chemotherapy regimens and outcome measures, are summarized in Table 1.…”
Section: Characteristics Of Included Trialsmentioning
confidence: 99%
“…Computed Tomography or magnetic resonance imaging scans were performed at the baseline. The response was assessed by the investigators according to the Response Evaluation Criteria in Solid Tumors (RECIST), version 1.0 (23)(24)(25)(26).…”
Section: Characteristics Of Included Trialsmentioning
confidence: 99%
See 1 more Smart Citation